The use of HPV-DNA testing combined with Pap smear in detection of pre-invasive disease of the cervix - Nwesar, Fayrouz A.; Salam T., Tawfik Abdel; M., Marwa Hanafi; Younis, Layla K.; Abou-Zeid, Ziad S.; Elkaffash, Dalal M. N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cancer cervix constitutes a major health problem worldwide. It is one of the most common female malignancy in both incidence and mortality. Cancer cervix has many risk factors, the most important one is persistent infection with one of HPV high risk types. Its morbidity and mortality can be reduced by frequent screening and early diagnosis. So that, several studies have been conducted in recent years in order to find better tests for screening for pre-invasive disease of the cervix and so early intervention and better prognosis. This study aimed to compare the sensitivity of Pap test and HPV DNA test as screening tests for pre-invasive disease of the cervix. Methods: 100 females from those attending Alexandria University gynaecologic clinic for causes rather than cancer cervix were subjected to Pap smear and cervical swab for HPV-DNA testing at the same setting. Cases of HSIL or positive HPV were subjected to VIA test, colposcopy and cervical punch biopsy was taken if aceto-whitening of the cervix or any other abnormality was found. Cases with ASCUS or LSIL were re-smeared after 3-6 months, if persistent or progressive pathology, colposcopy and punch biopsy from acetowhite areas were taken. Results: 21 cases (21%) were HPV positive and 66 cases (66%) were positive for intraepithelial lesions (37% ASCUS, 18% LSIL and 11% HSIL) with re-smearing there were 3 persistent ASCUS cases (8.1%) and 5 LSIL cases (27.78%). Colposcopy done, and biopsies were taken from 10 HSIL cases (90.1%), 5 LSIL (27.8%), 3 ASCUS (8.1%) and 10 HPV positive cases (62.5%). With significant relationship between colposcopic findings and HPV-DNA positivity and abnormal cytology. Biopsies were 18; 14 were CIN I and 4 were CIN II. Conclusions: HPV-DNA positivity has positive association with HSIL. Pap smear is an easy cheap method for screening. HPV-DNA test is less sensitive than cytology as a method for screening.